Implementasi Layanan Bimbingan Kelompok dalam Meningkatkan Disiplin Mahasiswa BK - Azhar; Enny Fitriani; Nurasyah (JKI (Jurnal Konseling Indonesia), 2020)
The importance of self-discipline for everyone, especially new teenagers, will form a complete personal pattern in developing their potential. This study aims to improve student discipline through the application of Group Guidance Services. The research method used in this study is a quasi-experimental research method. The study population numbered 45 students, the total sample of 10 students selected by simple random sampling technique. This research uses an instrument in the form of a discipline questionnaire with a Likert scale type. Data were analyzed through T-test. The results showed that from the initial test data, the average discipline attitude of students was 86 and after being treated in the form of group guidance services, the average discipline behavior of students increased to 132.5, the increase in discipline attitude was 46.5 points. The results of implementing BK assessments based on group guidance services have a significant positive impact on student discipline.